2022
DOI: 10.1016/j.ecns.2021.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Situational Awareness Differences Between Novice and Expert Nurses: Is There a Correlation With Clinical Judgment?

Abstract: Background: This study sought to explore situation awareness (SA) differences between novice and expert nurses and determine if there was a correlation between the SA and clinical judgment. Method: This was a multi-site study that used a comparative design with a known groups approach. Eye tracking glasses provided visual attention data. Results: There was a significant attention difference between groups in looking at the SpO2 value and the provider orders. A negative relationship was found between looking at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…A total of 23 articles reported the use of eye trackers in the comparison of visual attention or stress/cognitive load between different levels of nursing experience groups, including a comparison between nursing students and registered nurses and between novice and expert or experienced nurses, whose results would be used as nurses or nursing students education. The experimental tasks included surgical counts (Koh et al., 2009 ), management of patient deterioration (Al‐Moteri et al., 2020 ; Shinnick, 2016 , 2021 , 2022 ), analysing electrocardiographs (Broadbent et al., 2014 ), using a closed‐loop ventilation system (Buehler et al., 2021 ), caring for a decompensated heart failure patient (Cabrera‐Mino et al., 2019 ), injection/infusion/blood collection/intravenous catheterization (Cai et al., 2022 ; Kataoka et al., 2011 ; Maekawa et al., 2016 ; Mihara et al., 2020 ; Parker et al., 2021 ; Sugimoto et al., 2022 ), observation of psychopathological symptoms (Chiba et al., 2021 ), seizure recognition (Fogarasi et al., 2010 ), medication administration (Badeaux, 2015 ), interpretation of simulated vital signs (Currie et al., 2018 ), performing sterile technique (Hayashi et al., 2018 ), experience within surgery (Koh, Park, et al., 2011 ), handling of needles (Sanchez et al., 2019 ), endotracheal suctioning (Takeuchi et al., 2019 ), and information gathering (Suetsugu et al., 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 23 articles reported the use of eye trackers in the comparison of visual attention or stress/cognitive load between different levels of nursing experience groups, including a comparison between nursing students and registered nurses and between novice and expert or experienced nurses, whose results would be used as nurses or nursing students education. The experimental tasks included surgical counts (Koh et al., 2009 ), management of patient deterioration (Al‐Moteri et al., 2020 ; Shinnick, 2016 , 2021 , 2022 ), analysing electrocardiographs (Broadbent et al., 2014 ), using a closed‐loop ventilation system (Buehler et al., 2021 ), caring for a decompensated heart failure patient (Cabrera‐Mino et al., 2019 ), injection/infusion/blood collection/intravenous catheterization (Cai et al., 2022 ; Kataoka et al., 2011 ; Maekawa et al., 2016 ; Mihara et al., 2020 ; Parker et al., 2021 ; Sugimoto et al., 2022 ), observation of psychopathological symptoms (Chiba et al., 2021 ), seizure recognition (Fogarasi et al., 2010 ), medication administration (Badeaux, 2015 ), interpretation of simulated vital signs (Currie et al., 2018 ), performing sterile technique (Hayashi et al., 2018 ), experience within surgery (Koh, Park, et al., 2011 ), handling of needles (Sanchez et al., 2019 ), endotracheal suctioning (Takeuchi et al., 2019 ), and information gathering (Suetsugu et al., 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the sampling rates of some devices are certain, it is recommended to report the sampling rates so that readers do not need to read more materials to grasp this information. The highest sampling rate is 500 Hz (Badeaux, 2015 ), and the lowest sampling rate is 24 Hz (Shinnick, 2021 , 2022 ). 30 Hz ( N = 6) and 60 Hz ( N = 6) are more common.…”
Section: Resultsmentioning
confidence: 99%
“…While Hunter et al (2020) found the notion to be appropriate for paramedicine, Steen-Tveit and Munkvold (2021) found it challenging to build a Common Operational Picture and argued that what efficient collaboration requires is a common situational understanding, which does not equate to shared information. In a study of nurses, Shinnick (2022) found Situational Awareness to vary even among more and less experienced colleagues in the same team, suggesting a correlation between Situational Awareness and clinical judgment. Hence, there is still much to explore about the relation between individual and group perceptions of the same situations and how organizational structures and management systems can do to promote and sustain mindful organizing for safety across organizational borders.…”
Section: Management Control Of Doctrines For Occupational Health and ...mentioning
confidence: 99%
“…Effective clinical judgment involves nurses recognizing, interpreting, and acting on cues [2]. However, previous studies on novice nurses' clinical judgment skills revealed the following: novice nurses are aware of fewer cues than experienced nurses, which may hinder their ability to identify patient problems in clinical judgment [3]; lack the correct recognition of situations and priorities [2,4]; lack the ability to identify important data [5]; and have few reasoning patterns [6]. This inexperience in clinical judgment skills affects safe patient care [7].…”
Section: Introductionmentioning
confidence: 99%